Decreasing severe pain and serious adverse events while moving intensive care unit patients: a prospective interventional study (the NURSE-DO project) - de Jong, Audrey (BioMed Central, 2013)
INTRODUCTION: A quality-improvement project was conducted to reduce severe pain and stress-related events while moving ICU-patients. METHODS: The Plan-Do-Check-Adjust cycle was studied during four one-month phases, separated by five-month interphases. All consecutive patients staying more than 24 hours were evaluated every morning while being moved for nursing care (bathing, massage, sheet-change, repositioning). Phase 1 was considered as the baseline. Implemented and adjusted quality-interventions were assessed at phases 2 and 3, respectively. An independent post-intervention control-audit was performed at Phase 4. Primary-endpoints were the incidence of severe pain defined by a behavioral pain scale > 5 or a 0 to 10 visual numeric rating scale > 6, and the incidence of serious adverse events (SAE): cardiac arrest, arrhythmias, tachycardia, bradycardia, hypertension, hypotension, desaturation, bradypnea or ventilatory distress. Pain, SAE, patients' characteristics and analgesia were compared among the phases by a multivariate mixed-effects model for repeated-measurements, adjusted on severity index, age, admission type (medical/surgical), intubation and sedation status. RESULTS: During the four studied phases, 630 care procedures were analyzed in 53, 47, 43 and 50 patients, respectively. Incidence of severe pain decreased significantly from 16% (baseline) to 6% in Phase 3 (odds ratio (OR) = 0.33 (0.11; 0.98), P = 0.04) and 2% in Phase 4 (OR = 0.30 (0.12; 0.95), P = 0.02). Incidence of SAE decreased significantly from 37% (baseline) to 17% in Phase 3 and 21% in Phase 4. In multivariate analysis, SAE were independently associated with Phase 3 (OR = 0.40 (0.23; 0.72), P < 0.01), Phase 4 (OR = 0.53 (0.30; 0.92), P = 0.03), intubation status (OR = 1.91 (1.28; 2.85), P < 0.01) and severe pain (OR = 2.74 (1.54; 4.89), P < 0.001). CONCLUSIONS: Severe pain and serious adverse events are common and strongly associated while moving ICU patients for nursing procedures. Quality improvement of pain management is associated with a decrease of serious adverse events. Careful documentation of pain management during mobilization for nursing procedures could be implemented as a health quality indicator in the ICU.